Uporaba tehnologije eksplozijskega navarjanja v postopku izdelave hidravličnih valjev - Jovišević, Vid (Strojniški vestnik, 2005)
This paper treats the technologies for glide-pairs forming using bronze cladding and using the sheet-bronze explosive cladding technique over the glide surfaces of a steel hydraulic cylinder. In the paper the microhardness, the microstructure and the bond strength of the interface of a bi-metallic joint on the cross-section of the test hydraulic cylinder were investigated. A parallel results survey of the application of these two technologies is shown based on metallographic and mechanical investigations of the interface between the CuSn6 bronze and the TS5 steel cylinder.
Keywords: navarjanje eksplozijsko; valji hidravlični; trdnost strižna; plasti mejne; broni-jekla; eksplozijsko navarjanje; hidravlični valji; mehanske lastnosti; metalografske preiskave